Forward Foreign Exchange Rates, Expected Spot Rates, and Premia: A Signal‐Extraction Approach - WOLFF, CHRISTIAN C. P. (Journal of Finance, 1987)
ABSTRACT In this paper, we implement a methodology to identify and measure premia in the pricing of forward foreign exchange that involves application of signal‐extraction techniques from the engineering literature. Diagnostic tests indicate that these methods are quite successful in capturing the essence of the time‐series properties of premium terms. The estimated premium models indicate that premia show a certain degree of persistance over time and that more than half the variance in the forecast error that results from the use of current forward rates as predictors of future spot rates is accounted for by variation in premium terms. The methodology can be applied straightforwardly to the measurement of unobservables in other financial markets.